Hubungan Antara Kadar Hormon Dengan Perdarahan Di Luar Siklus Menstruasi Pada Wanita Usia Subur - ningsih, sri mudayati; Suryandari, endang sri dewi hastuti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Bleeding disorders outside the menstrual cycle are reproductive system disorders commonly experienced by women during their reproductive years. These disorders are characterized by changes in menstrual periods, including alterations in cycle length, duration of menstruation, or volume of bleeding, with a worldwide prevalence ranging from 3% to 30%. Hormonal factors are often implicated as causes of bleeding disorders outside the menstrual cycle. Preliminary findings from a study conducted at RSIA Puri revealed that three female patients seeking treatment experienced bleeding disorders outside the menstrual cycle, with two of them exhibiting low estrogen levels (below 20 pg/ml) upon examination. The purpose of this study was to analyze the relationship between hormone levels, particularly estrogen, and bleeding outside the menstrual cycle in women of childbearing age at RSIA Puri Malang. The research employed a quantitative analysis through a cross-sectional approach. Primary and secondary data were obtained from laboratory examinations of estrogen levels in blood serum on the third day of menstruation. The sample consisted of 34 mothers who met the criteria of experiencing menstrual disorders and visited RSIA Puri Malang, and who willingly participated as respondents, selected through quota sampling. Data analysis was conducted using the Chi-square test, and the results revealed a significant relationship between estrogen levels and bleeding outside the menstrual cycle, or metrorrhagia (p-value = 0.018; OR = 0.107). This suggests that estrogen hormone regulation plays a crucial role in preventing menstrual irregularities. In conclusion, maintaining optimal estrogen hormone levels is essential for preventing and managing menstrual irregularities and bleeding disorders outside the menstrual cycle.